MEDU-43. GLOBAL AND REGIONAL EFFECTS OF RADIATION THERAPY ON CEREBRAL MICROVASCULATURE IN PEDIATRIC BRAIN TUMOR SURVIVORS. (23rd April 2019) - Avadiappan, Sivakami; Morrison, Melanie; Jakary, Angela; Felton, Erin; Stoller, Schuyler; Hess, Christopher; Mueller, Sabine; Braunstein, Steve; Lupo, Janine
Abstract: INTRODUCTION: Although cranial radiation therapy (RT) is a common treatment for pediatric brain tumors, it can have long-term effects such as cognitive decline and vascular injury in the form of cerebral microbleeds (CMBs). As pediatric brain tumor patients' survival is now extending into adulthood, it is increasingly important to understand the impact of vascular injury due to RT on their cognitive function. METHODS: 15 patients (ages 10–24) treated with whole-brain or whole-ventricular RT for infratentorial pediatric brain tumors (Medulloblastoma, Germinoma, Anaplastic Ganglioglioma) 2 months to 16 years prior, and 3 non-irradiated control patients (ages 14–26) were scanned on a 7 Tesla MRI scanner using a novel simultaneous MRA-SWI acquisition that enabled visualization of arteries, veins, and CMBs on one image. Arteries were segmented from the MRA and the resulting distribution of vessels in different brain lobes and white matter was correlated with cognitive performance and compared among the two RT treatment groups and the non-irradiated control group. RESULTS: Global arterial volume, normalized by brain volume, was significantly reduced with increasing RT treatment volume (p<0.02) and decreased with the number of CMBs and over time. The executive function score from Cogstate test was significantly lower in patients with smaller arterial vessel volume than average (p<0.02). Local vessel volume (normalized by regional brain volume) reduced uniformly across all brain lobes for patients who received whole-brain RT compared to the non-irradiated control patients. Patients who received whole-ventricular RT had reduced vessel volume only in the occipital and temporal lobes, which were within the treatment field. Although CMBs were located closer to veins than arteries, their size increased with distance from the nearest vessel. CONCLUSIONS: Our findings suggest that spatial variations in vascular morphology are related to the presence and size of CMBs, depend on the RT treatment volume, and may affect cognitive function.